Perceptual learning style preference (PLSP) to learn grammar among students of selected secondary schools in Shah Alam / Nurul Nadia Rasdi - Rasdi, Nurul Nadia (2013)
Students face difficulty in learning grammar. In order to learn grammar effectively in the classroom, teachers have to consider the students’ learning style. When students’ learning style is catered to, they will show positive achievement towards what they had learnt. Therefore, this study is set out to investigate students’ major, minor, and negligible learning style preference to learn grammar. It is also to examine students’ learning style between male and female students in the classroom. The study further explores teachers’ teaching style from the students’ perspective. Students who participated in this study are 244 Form 1 students of selected secondary schools in Shah Alam. To elicit information from the students, Perceptual Learning Style Preference Questionnaire (Reid, 1984) was administered. The data obtained was analysed using descriptive statistics and an independent sample t-test. The findings reveal that students in general favour group, kinaesthetic, tactile, visual, and auditory (major), as well as individual (minor) learning style. Male students favour group, kinaesthetic, tactile, visual, and auditory learning style. In contrast, female students favour all the learning styles. However, there is a slight mismatch between students’ learning style and teachers’ teaching style preferences. Hence, the findings of this study indicate that teachers should be aware of students’ learning style so that the teaching and learning of grammar in the classroom will be more effective.